Factors influencing the need for post operative ventilation in patients with aneurysmal subarachnoid hemorrhage - Bohara, Sandeep; Thapa, Amit (Nepal Journal of Neuroscience, 2023)
Introduction: Patients with aneurysmal subarachnoid hemorrhage (aSAH) frequently require monitoring, however planned ventilatory support may not be necessary in the post-operative period. In resource constraints scenarios, reserving an intensive care unit (ICU) bed and ventilator may lead to problems like delay in surgery and definite care. With this study, we aim to identify the factors that influence the need for post-operative ventilation in patients with aSAH.Methodology: A retrospective study over a period of six years of patients who underwent surgical clipping of aneurysm and were not intubated pre-operatively was conducted. Aneurysm was confirmed by Digital Subtraction Angiography (DSA) or Computerized Tomographic Angiography (CTA). Demographic data and clinico-radiological factors like Hunt and Hess grade, Modified Fischers Grade and aneurysm location were collected.Results: Of the 62 patients identified in the study period, 17 patients were excluded as they were intubated in the preoperative period. Of the 45 patients included, there were 15 male patients. Of these only 23 (51.11%) patients failed to be successfully extubated. Clinical factors such as Hunt and Hess score ≥ 3 (p value